How to make a Hill Plot - Holger Drees; Laurens F.M. de Haan; Sidney Resnick (Tinbergen Institute, 1998)
An abundance of high quality data sets requiring heavy tailed models necessitates reliablemethods of estimating the shape parameter governing the degree of tail heaviness.The Hill estimator is a popular method for doing this but its practical use isencumbered by several difficulties. We show that an alternative method of plotting Hillestimator values is more revealing than the standard method unless the underlyingdata comes from a Pareto distribution.
Keywords: 330; Schätztheorie; Wahrscheinlichkeitsrechnung; Theorie